Clothes, conventions and modernity. Rudofsky ?s exhibition at the MoMA - Anita Puig Gómez (Materia Arquitectura)
This article presents the debate on the formulation and the original proposals regarding Bernard Rudofsky s 1944 exhibition for the Museum of Modern Art of New York. Through the analysis of the original letters sent by the architect during the research and curatorship of the exhibition, the research history, and the objects that did not make it to the show, it is possible to conclude that the exhibition ends up conforming to the conventions that modern architecture posed, exactly those that Rudofsky aimed to criticize. The exhibition established a dialogue between clothes and rationalized body, that turned out critical specifically among the difficult times after the end of Second World War.